Hammer throwing: dynamic aspects of the lower extremeties - Maheras, A. V. (Techniques Magazine, 2018)
During the course of a hammer throw, the thrower will turn with the hammer three or four times alternating between double and single support. In this fashion, the left foot ist always in contact with the ground. The right foot spends a good part of the total turn time off the ground, the actual time depending primarily on the skill of the thrower and also the order of a particular turn. The forces exerted by the feet on the ground will allow the thrower to, in turn , successfully impact the optimum amount of force on the hammer itself. An observation of the action of the right foot in hammer throwers will show that some prefer to execute a "stomping" action, as that foot comes in contact with the ground to complete a turn, while others choose to bring it in contact with the ground in a "softer" or neutral fashion during that phase. The action of the feet, and particularly the right foot, from a dynamic point of view, will be discussed below.